Case report: A novel 11-bp deletion in exon 11 causing a frameshift in the C-terminal of the ALAS2 gene leading to X-linked sideroblastic anemia—a family study - Al kindi, Salam; Al-Mamari, Altaf; Al-Zadjali, Shoaib; Al-Rawahi, Mohamed; Al Madhani, Ali; Pathare, Anil V. (Frontiers in Medicine, 2025)
X-linked Sideroblastic Anemia (XLSA) (MIM 300752) is the most common genetic form of sideroblastic anemia, a heterogeneous group of disorders characterized by iron deposits in the mitochondria of erythroid precursors. It is due to mutations of the erythroid-specific enzyme ALAS2, the first enzyme of the heme biosynthetic pathway. Here we report a novel 11-bp del in exon 11 leading to a frameshift in the C-terminal region of ALAS2 gene with a nonfunctional longer polypeptide of 614 amino acids leading to a loss of function mutation manifested as an X-linked sideroblastic anemia phenotype. The proband was a 29-year-old man with moderately severe microcytic hypochromic anemia with splenomegaly and an increased ring sideroblasts in the bone marrow with considerable iron overload.Sanger sequencing documented a missense mutation leading to a frameshift with an elongated polypeptide of 614AA instead of the normal 587AA protein c.1743_1753del, p. (Gln581Hisfs*35) (pGln581HisfsX35). This mutation affected the interaction with cofactor pyridoxal 5'-phosphate since the patient improved his hemoglobin with oral administration of pyridoxine tablets. His iron overload also responded to sustained oral iron chelation therapy with Deferasirox. Screening of the entire family kindred revealed that two other male siblings were also hemizygous for the same mutation with hypochromic microcytic anemia and tissue iron overload, whereas, three female siblings and their mother were heterozygous for the mutant allele. They did not have anemia or iron overload.